AVALIAÇÃO DA PROLIFERAÇÃO CELULAR E ESPESSURA DO ENDOMÉTRIO DE CADELAS EM DIFERENTES PERÍODOS DO DIESTRO - Gossler, Vanessa da Silva Alves (2015)
This study aimed to determine the histological features of the endometrium of biches, as well as the cell proliferation at specific moments of diestrus, 10, 20, 30, 40, 50 and 60 days post-ovulation, correlating the endometrial thickness with the uterine cell proliferation and the metabolic state (weight, blood glucose and plasma cholesterol) of the animals. Therefore, the right and left uterine horns of 26 clinically healthy bitches submitted to ovariohysterectomy were histologically analyzed 10, 20, 30, 40, 50 and 60 days post-ovulation. The hematoxylin-eosin and AgNOR staining techniques were performed. All parameters were evaluated by the Shapiro-Wilk normality assumption and the samples subjected to ANOVA and post-hoc Tukey test (p<0.05). The correlation between endometrial thickness and uterine cell proliferation, weight, blood glucose and plasma cholesterol of animals was observed using the Pearson method (p<0.05). The software used was BioEstat® version 5.0. It was concluded that the endometrial thickness did not differs between post-ovulation days and was not correlated with the uterine cell proliferation, weight, blood glucose or serum cholesterol of the bitches. However, there was greater cell proliferation at 40 days post-ovulation compared to 60 days.